Natural Justice And The Constitution: Recent Cases From The Court Of Appeal - Crook, Peter S (Journal of Malaysian and Comparative Law, 2019)
The doctrine of natural justice has long been a bulwark against the arbitrary exercise of administrative power. Since its modern rebirth with Ridge v Baldwin in the 1960s the English common law courts have construed a formidale body of case law defining the procedural constraints under which administrative power must operate.